2015
DOI: 10.1111/aogs.12767
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of postoperative pain after transumbilical single‐port access and conventional three‐port total laparoscopic hysterectomy: a randomized controlled trial

Abstract: SPA-TLH was feasible compared with MPA-TLH but the SPA-TLH group had a longer operative time. Although there is no difference in pain based on the visual analog scale pain score, the SPA-TLH group required more analgesia to give the same postoperative pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…Prior studies have reviewed the proposed benefits of a vNOTES approach including better visualization of pelvic structures compared to traditional vaginal procedures, lower pain scores, and improved cosmesis, owing to the lack of an abdominal incision [8,9]. However, many of these studies have small sample sizes and are limited in their generalizability with data derived from a single institution [26][27][28][29][30][31][32][33]. We sought to systematically review the current literature to compare the safety and efficacy of conventional multiport laparoscopic (MPL) hysterectomy both to LESS and vNOTES approaches to determine if one approach is associated with improved patient outcomes, within a larger, more heterogeneous sample of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have reviewed the proposed benefits of a vNOTES approach including better visualization of pelvic structures compared to traditional vaginal procedures, lower pain scores, and improved cosmesis, owing to the lack of an abdominal incision [8,9]. However, many of these studies have small sample sizes and are limited in their generalizability with data derived from a single institution [26][27][28][29][30][31][32][33]. We sought to systematically review the current literature to compare the safety and efficacy of conventional multiport laparoscopic (MPL) hysterectomy both to LESS and vNOTES approaches to determine if one approach is associated with improved patient outcomes, within a larger, more heterogeneous sample of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing single-port surgery versus minilaparotomy were mixed, with one study reporting less pain in the single-port group,51 while others finding no difference 52 53. Chung and colleagues54 reported more rescue analgesics in the single-port group when it was compared with a standard three-port surgery while other studies found no difference in pain scores or analgesics 55 56. Compared with single-port hysterectomy, minilaparoscopy led to lower pain scores in one study 57.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, it cannot be excluded that enrolled patients in the study are biased with respect to their pain outcomes as, except in one study, the included patients were not blinded to the type of surgery. One single randomized controlled trial applied accurate blinding [20]. Patients and anesthesiology staff who measured the postoperative pain scores did not know which type of approach had been performed, while similar pain scores were found.…”
Section: Discussionmentioning
confidence: 99%